HUBUNGAN PENGETAHUAN ORANGTUA DENGAN PERILAKU PENGGUNAAN FIRST AID KITS DALAM PENANGANAN CIDERA TODDLER - Pasaribu, Dewi Astuti; Sembiring, Elyani; Zai, Alvared Rahmadani (Universitas Prima Indonesia, 2023)
The role of parents is very important in having knowledge of the proper behavior of using First Aid Kits in treating injuries in toddlers. Toddlers aged 12-36 months are at risk of injury. The purpose of this study was to identify the relationship between the level of parental knowledge and the behavior of using First Aid Kits in treating injuries in toddlers. The research design is descriptive correlation with a cross sectional approach (cross tabulation). The research sample was 37 parents (respondents) who had toddler-aged children. In this study, the frequency distribution of the relationship (correlation) level of parental knowledge with the use of First Aid Kits showed that the majority of respondents were in the category with a “high” level of parental knowledge and the use of First Aid Kits in the